2016
DOI: 10.1099/jmm.0.000205
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal effect of Er:YAG laser combined with sodium hypochlorite irrigation against Enterococcus faecalis deep inside dentinal tubules in experimentally infected root canals

Abstract: This study evaluated the bactericidal effect of Er:YAG laser radiation combined with sodium hypochlorite (NaOCl) irrigation in the treatment of Enterococcus faecalis deep inside dentinal tubules. The Er:YAG laser was activated, respectively, at 0.3, 0.5 and 1.0 W for either 20 or 30 s; 52.5 g l 21 NaOCl and normal saline were used for the control groups. Root canals before and after treatments were examined using scanning electron microscopy (SEM). Bacterial reductions both on the root canal walls and at 100, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…The mechanical effect of LAI was shown to be stronger than ultrasonic activation during the physical removal of a biofilm-mimicking hydrogel (water as irrigant) [14] and of a dual species biofilm ( S. mutans and E. faecalis ) (saline as irrigant) [15], which was attributed to the extremely turbulent action of the irrigation solutions activated with a pulsed erbium laser; consequently, when NaOCl was used as an irrigant, the reductions were superior to the results obtained with saline and both LAI and ultrasound did no show significant differences any more [15]. 15Although not statistically significant, together with data from other studies the final number of bacteria left was lower, the final amount of reduction was higher or more negative samples were seen with LAI [31,34,36,44,45,46,47,48]. The same phenomenon is also seen in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical effect of LAI was shown to be stronger than ultrasonic activation during the physical removal of a biofilm-mimicking hydrogel (water as irrigant) [14] and of a dual species biofilm ( S. mutans and E. faecalis ) (saline as irrigant) [15], which was attributed to the extremely turbulent action of the irrigation solutions activated with a pulsed erbium laser; consequently, when NaOCl was used as an irrigant, the reductions were superior to the results obtained with saline and both LAI and ultrasound did no show significant differences any more [15]. 15Although not statistically significant, together with data from other studies the final number of bacteria left was lower, the final amount of reduction was higher or more negative samples were seen with LAI [31,34,36,44,45,46,47,48]. The same phenomenon is also seen in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Two-thirds of them (11/18) concluded that PIPS had high bacterial killing efficacy, which was significantly more effective than CSI. [31][32][33][34][35][36][37][38][39][40] This was also more effective than several other activation techniques including PUI, 31,35 Nd:YAG irradiation, 39 EndoActivator, and XP-endo Finisher file. 37 One study found that PIPS coupled with 6% NaOCl inhibited 100% of E. faecalis but did not compare it to other techniques.…”
Section: Debris Removalmentioning
confidence: 86%
“…They concluded that the most efficient methods were activation with 0.5 and 1.0 W for 30 seconds. 38 Laser activation at 0.5 W for 30 seconds combined with NaOCl is the preferable option because of the lower emission power. In addition, PIPS used at either 10 or 20 mJ and 0.3 or 0.9 W produced a similar apical extrusion volume.…”
Section: Apical Extrusionmentioning
confidence: 99%
“…Our findings can probably be explained by the increased fluid dynamics that lead to biomechanical intracanal cleaning and by an easier penetration of the irrigant into deeper dentine layers caused by Er:YAG laser-induced cavitation effects. 1,9,41 It was shown that the penetration of A. oris into the dentinal tubules in the presence of S. gordonii was much deeper than in a mono-infection model. 31 The LAI 600 setting was most active in reducing bacteria from dentinal tubules especially for A. oris/S.…”
Section: Endodontic Disinfection With Er:yag Laser Discussionmentioning
confidence: 99%
“…For this purpose, the irrigation with disinfecting agents is strongly recommended as an additional step to remove and kill pathogens inside dentinal tubules. 1,2 Sodium hypochlorite (NaOCl) is the most commonly used endodontic irrigating solution in the dental practice owing to its antimicrobial and proteolytic properties and its excellent ability to dissolve organic tissue. 3 Despite these favorable properties, the irrigation with NaOCl as an adjuvant to root canal preparation cannot completely remove microorganisms from the dentine and consequently allows for persistent endodontic infections.…”
Section: Introductionmentioning
confidence: 99%